Histopathological Study of The Upper Gastrointestinal Tract Endoscopic Biopsies - Somani, Neha Satyanarayan; Patil, Purwa (Annals of Pathology and Laboratory Medicine, 2018)
Background Patients presenting with gastrointestinal (GI) symptoms are very common in clinical practice. The advent of modern flexible endoscopes has made entry as well as visualization inside the upper GI tract easy, thereby facilitating the effective management of these patients. This study was conducted to determine the frequency as well as to study the spectrum of the histopathological lesions of upper GI tract. The clinical symptoms, endoscopic findings, and histopathological findings were also correlated. Methods This is a cross sectional study conducted in the Department of Pathology, in a tertiary care hospital, from July 2014 to June 2016. All the full mucosal thickness endoscopic biopsies, incorporating muscularis mucosae, of the upper GI tract were included in the study. Results The upper GI endoscopic biopsies constituted 0.93% of all surgical pathology specimens. Stomach was the most common biopsied site (55%), followed by esophagus (39%), and duodenum (6%). In esophagus, squamous cell carcinoma (82.60%) was more common as compared to adenocarcinoma (17.40%). Amongst gastric carcinoma, most common histological pattern noted was tubular adenocarcinoma (61.90%), followed by poorly cohesive carcinoma. All the duodenal biopsies showed chronic non-specific duodenitis. Overall, 91% concordance was noted between endoscopic and histopathological diagnosis. Conclusions Upper GI endoscopy is an effective and appropriate initial investigation to assess patients with upper GI symptoms. Histopathology is the gold standard for the diagnosis of endoscopically detected lesions.